Response time to estrus synchronization - Schalles, R.R.; Spire, M.; Clarke, Colleen Kay (Kansas State University. Agricultural Experiment Station, 2010)
Heavy milking cows took longer to respond to estrus synchronization than light milking cows. There was no difference in response time between cows treated with Estrumate and Lutalyse. Cow weight, height or condition had no effect on estrus response time.
Keywords: Beef; Estrus; Milk production